The Effect of Family Social Support and School Climate on Students’ Learning Motivation - Sri Wahyuni; Ana Nur Dunya Azizah; Nila Zaimatus Septiana (Edudeena : Journal of Islamic Religious Education, 2022)
Abstract: This study is intended 1) to determine the effect of family social support on students’ motivation to learn Islamic education, 2) to determine the effect of school climate on students’ motivation to learn Islamic education, 3) to find out the effect of family social support and school climate on students’ motivation to learn Islamic education. This study uses a quantitative approach through correlation research design. The subject of this study is the eighth grade students of SMP Negeri 1 Ngadiluwih. The sample used is 175 students using simple random sampling technique. The data are analyzed by using simple and multiple linier regression analysis. The results of the study show that 1) there is an influence of family social support on student motivation to learn Islamic education which has an effect of 18.2 percent, and the remaining 81.8 percent is influenced by other factors; 2) there is an influence of school climate on students’ motivation to learn Islamic education which has an effect of 17.4 percent, and the remaining 82.6 percent is influenced by other factors; 3) there is an influence of family social support and school climate on students’ motivation to learn Islamic education which has an effect of 23.2 percent, and the remaining 76.8 percent is influenced by other factors. Abstrak: Penelitian ini dimaksudkan 1) untuk mengetahui pengaruh dukungan sosial keluarga terhadap motivasi belajar pendidikan agama Islam, 2) untuk mengetahui pengaruh iklim sekolah terhadap motivasi belajar pendidikan agama Islam. 3) untuk mengetahui pengaruh dukungan sosial keluarga dan iklim sekolah terhadap motivasi belajar pendidikan agama Islam. Penelitian ini menggunakan pendekatan kuantitatif desain korelasi. Subjek penelitian ini siswa kelas VIII SMP Negeri 1 Ngadiluwih. Sampel yang digunakan berjumlah 175 siswa menggunakan teknik simple random sampling. Analisis data menggunakan analisis regresi linier sederhana dan berganda. Hasil penelitian menunjukkan 1) ada pengaruh dukungan sosial keluarga terhadap motivasi belajar pendidikan agama Islam yang berpengaruh sebesar 18,2 persen dan sisanya yaitu 81,8 persen dipengaruhi faktor lain; 2) ada pengaruh iklim sekolah terhadap motivasi belajar pendidikan agama Islam yang berpengaruh sebesar 17,4 persen dan sisanya yaitu 82,6 persen dipengaruhi faktor lain; 3) ada pengaruh dukungan sosial keluarga dan iklim sekolah terhadap motivasi belajar pendidikan agama Islam yang berpengaruh sebesar 23,2 persen dan sisanya yaitu 76,8 persen dipengaruhi faktor lain.